2018
DOI: 10.1007/s40617-018-00301-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Behavior Readings Assigned by Accredited Master’s Degree Programs in Behavior Analysis

Abstract: Although a foundation in the basic science of behavior represents a common goal of practitioners and educators of behavior analysis, the content covered in master's degree-level courses on the experimental analysis of behavior (EAB) can vary widely across university programs. The purpose of our study was to analyze the syllabi of master's degree programs accredited by the Association for Behavior Analysis International to develop a list of common readings and topics in EAB coursework that might be useful for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…With specific focus on training in experimentation, Kazemi et al (2019) conducted an analysis of syllabi across 70% of the 20 ABAI-accredited programs in order to examine assigned readings in experimental analysis of behavior (EAB) across programs. Although this study identified a list of common readings (specific books, chapters, and journal articles) by EAB topic area, it also identified variability beyond those common readings, and that instructors were more likely to assign applied or subspeciality topics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With specific focus on training in experimentation, Kazemi et al (2019) conducted an analysis of syllabi across 70% of the 20 ABAI-accredited programs in order to examine assigned readings in experimental analysis of behavior (EAB) across programs. Although this study identified a list of common readings (specific books, chapters, and journal articles) by EAB topic area, it also identified variability beyond those common readings, and that instructors were more likely to assign applied or subspeciality topics.…”
mentioning
confidence: 99%
“…Although Kazemi et al (2019) focused primarily on EAB content areas, Pastrana et al (2018) conducted a similar analysis of course syllabi and reported the 10 most frequently assigned readings from the VCS programs with pass rates of 80% or higher and at least six first-time test-takers and (if the program had fewer than six first-time test-takers, the previous year's 2013 pass rate was combined with the 2014 pass rate). Although the authors framed the results of this analysis as a resource for curriculum developers, they also stated, "the pass rate of an institution is unlikely the most important dependent variable for graduate training.…”
mentioning
confidence: 99%